Evaluation of a Sustained-release Prednisolone Acetate Biodegradable Subconjunctival Implant in a Non-Human Primate Model - Liu, Yu-Chi (2018)
Purpose: We evaluate the toxicity and plasma toxicokinetic (TK) profile of a biodegradable subconjunctival microrod for sustained prednisolone acetate (PA) release over 12 weeks in a non-human primate model. Methods: The biodegradable copolymer poly(l-lactide-co-ε-caprolactone) (PLC) and 40-wt% PA microrods were used and fashioned into 8 and 16 mm lengths. Twelve monkeys were divided into two treatment groups of PA-loaded and blank microrods, with six monkeys each receiving either 8- or 16-mm microrods subconjunctively implanted into both eyes. TK and hematology parameters were analyzed. Ophthalmic clinical evaluation, including slit-lamp and ophthalmoscopy examinations, was performed. Results: Over the study period of 12 weeks, the mean area under the plasma concentration-time curve was 45.7% higher, and the maximum plasma concentration was 17.2% lower for the animals treated with 40-wt% PA 16-mm microrods compared to 8-mm microrods (251.44 versus 172.54 hours × nanograms per milliliter and 8.53 versus 10.30 ng/mL, respectively). The PA release was significantly below the levels of assumed toxicity. There was no significant difference in the time to reach maximum concentration between the 8- and 16-mm microrod groups (7.33 and 8 hours; P = 0.421). Findings from clinical evaluation, hematology, and histopathology showed no ocular side effects and no significant adverse systemic effects. Conclusion: The PA biodegradable microrods demonstrated safe toxicokinetics even with the larger size implant containing a higher amount of drug. The PA implant may be considered as a safe alternative to the application of topical PA eyedrops. Translational Relevance: The results provide the evidence of the safety of implanting a steroid delivery system subconjunctively, offering an alternative to topical PA eyedrops.